2015
DOI: 10.1158/1055-9965.epi-14-1396
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-Randomized Trial to Increase Hepatitis B Testing among Koreans in Los Angeles

Abstract: Background In the United States, Korean immigrants experience a disproportionately high burden of chronic hepatitis B (HBV) viral infection and associated liver cancer compared to the general population. However, despite clear clinical guidelines, HBV serologic testing among Koreans remains persistently sub-optimal. Methods We conducted a cluster-randomized trial to evaluate a church-based small group intervention to improve HBV testing among Koreans in Los Angeles. Fifty-two Korean churches, stratified by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 46 publications
0
57
0
1
Order By: Relevance
“…These differences may help to explain why our study achieved a significantly higher screening rate at 6 months of followup compared with other studies with various Asian American ethnic groups, in which screening rates among intervention group participants were <40%. 24,[28][29][30] The current study has several unique strengths that we believe led to the remarkably robust effect. First, the CBPR program was built on a well-established strong partnership between the CAH and Korean churches of the ACHC.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These differences may help to explain why our study achieved a significantly higher screening rate at 6 months of followup compared with other studies with various Asian American ethnic groups, in which screening rates among intervention group participants were <40%. 24,[28][29][30] The current study has several unique strengths that we believe led to the remarkably robust effect. First, the CBPR program was built on a well-established strong partnership between the CAH and Korean churches of the ACHC.…”
Section: Discussionmentioning
confidence: 82%
“…Second, the intervention approach used in the current study addressed both individual‐level and system‐level barriers. Compared with previous studies that focused primarily on individual education and motivation, the current study not only included intensive community education and direct involvement with community leaders in planning and organization, but also incorporated system‐based components, specifically patient navigation services (transportation assistance, appointment scheduling, language translation) and the active engagement of health care providers. The substantial barriers to health care access faced by Korean Americans include limited English proficiency, uninsured or underinsured status, low income, and a lack of familiarity with the US health care system .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a community‐based, randomized controlled trial among Hmong using bilingual/bicultural lay health workers, 24% of intervention participants reported receipt of HBV testing compared with 10% of controls . A church‐based, randomized controlled trial among Koreans with sessions led by lay health educators resulted in 19% of intervention participants reporting HBV testing, compared with 6% of controls . A study among Vietnamese Americans found that those who had received a physician's recommendation or requested HBV testing were 4 and 8 times more likely, respectively, to receive testing, indicating the need for both provider and patient education .…”
Section: Selected Findingsmentioning
confidence: 99%
“…134 A church-based, randomized controlled trial among Koreans with sessions led by lay health educators resulted in 19% of intervention participants reporting HBV testing, compared with 6% of controls. 135 A study among Vietnamese Americans found that those who had received a physician's recommendation or requested HBV testing were 4 and 8 times more likely, respectively, to receive testing, indicating the need for both provider and patient education. 136 As such, health system-based interventions also have the potential to improve HBV testing by leveraging the importance of provider recommendation and integrating electronic medical records.…”
Section: Infectious Agentsmentioning
confidence: 99%